2005
DOI: 10.1243/095440605x31463
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of Seams on the Aerodynamics of an Association Football

Abstract: * Corresponding author ABSTRACTThe aerodynamic properties of an association football were measured using a wind tunnel arrangement. A third scale model of a generic football (with seams) was used as well as a 'mini-football'. As the wind speed was increased, the drag coefficient decreased from 0.5 to 0.2, suggesting a transition from laminar to turbulent behaviour in the boundary layer. For spinning footballs, the Magnus effect was observed and it was found that reverse Magnus effects were possible at low Reyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 14 publications
0
37
0
Order By: Relevance
“…Such results have not been reported before for this type of ball. Carre et al [13], in experiments with footballs, concluded that there are no effects on C D due to ball orientation, but in that work the rotation of the ball was about the streamwise axis and could not therefore be expected to have an effect. Figure 7 shows the effect of orientation for the four real footballs.…”
Section: Fig 4 Ball Configurationsmentioning
confidence: 96%
“…Such results have not been reported before for this type of ball. Carre et al [13], in experiments with footballs, concluded that there are no effects on C D due to ball orientation, but in that work the rotation of the ball was about the streamwise axis and could not therefore be expected to have an effect. Figure 7 shows the effect of orientation for the four real footballs.…”
Section: Fig 4 Ball Configurationsmentioning
confidence: 96%
“…The tangential velocity at the ball surface, U T , is estimated by equation 9 with the radius equated at height, h, on the primary spin axis with -denoting the high pressure plate (B), and + denoting the low pressure plate (A): [9] The skin friction coefficient C F is also calculated separately for the high and the low pressure plate using the standard flat plate model and is given by: [10] Substituting into equation 8, the total force is given in equation 9: [11] Consequently the angular deceleration of the ball due to surface friction, with the total torque estimated to act at the centre of the plate, is given by: …”
Section: Figure 4 Centre Of Pressure During Flightmentioning
confidence: 99%
“…The wake structures were confirmed with flow visualisation. Earlier work by Carre 9 demonstrated that reverse Magnus effects are possible at low Reynolds numbers. The work was completed with a 1 / 3 scale rapid prototype football (66mm diameter) and a 'mini' football (140mm diameter adidas Fevernova™ Replica).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…For baseballs, the relationship between rotation and lateral forces was evaluated [3], as well as the effects of seams on their aerodynamic properties [4]. Several similar studies have investigated tennis balls [5], soccer balls [6][7][8], and cricket ball [9].…”
Section: Introductionmentioning
confidence: 99%